Malaysia's forest pledges and the Bornean State of Sarawak: a policy perspective - Koh, Jane; Johari, Shazali; Ahmad Shuib; Siow, May Ling; Matthew, Nitanan Koshy (Multidisciplinary Digital Publishing Institute, 2023)
Malaysia deforested 6.3 million hectares since independence; 91% of which occurred before Malaysia pledged, at the Earth Summit in 1992, to maintain a minimum 50% of its terrestrial area under forest cover. However, under economic and population pressure, Sarawak—the largest contributing state to the country’s current forest cover of 54.8%—shows continuing deforestation even after 1992. This paper reviews land use policies underpinned by economic development and environmental protection considerations, land rights issues that complicate land use planning, and legislation that regulates land use change. The objective is to investigate the adequacy of existing policies and legislation in governing forest cover in Sarawak and to recommend improvement measures. If the Sarawak Land Use Policy that allocates seven million hectares for forest is realized, Malaysia’s forest cover would drop to 53%, assuming other states maintain their forests. It is recommended that legislation governing the designation of permanent forest and conversion of forest for other land use to be strengthened, civil society to be enlisted to enhance knowledge level, and carbon credit production to be promoted as alternative land use that keeps forests standing. With these measures, it is hopeful that Malaysia’s aspirations regarding forest cover can be achieved.